2021
DOI: 10.1155/2021/9975296
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation and Modeling on CO2 Sequestration Coupled with Enhanced Gas Recovery in Shale Gas Reservoirs

Abstract: CO2 geological sequestration in shale is a promising method to mitigate global warming caused by greenhouse gas emissions as well as to enhance the gas recovery to some degree, which effectively addresses the problems related to energy demand and climate change. With the data from the New Albany Shale in the Illinois Basin in the United States, the CMG-GEM simulator is applied to establish a numerical model to evaluate the feasibility of CO2 sequestration in shale gas reservoirs with potential enhanced gas rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…These models have made some important predictions about the fate of the injected CO 2 , including how the injected CO 2 is partitioned among water, oil, gas, and mineral phases, how far and how quickly the injected CO 2 will migrate from its sources, how hydrocarbon production will be affected, and how the hydraulic properties of the reservoir will be changed. The results of these modeling studies broadly resemble those from other modeling studies from other sites [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionsupporting
confidence: 72%
“…These models have made some important predictions about the fate of the injected CO 2 , including how the injected CO 2 is partitioned among water, oil, gas, and mineral phases, how far and how quickly the injected CO 2 will migrate from its sources, how hydrocarbon production will be affected, and how the hydraulic properties of the reservoir will be changed. The results of these modeling studies broadly resemble those from other modeling studies from other sites [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionsupporting
confidence: 72%
“…As to the fluid flow within the hydraulic fracture, the Forchheimer model with the non-Darcy coefficient is implemented to simulate a turbulent flow, accounting for the inertial effects [16][17][18]. Meanwhile, local grid refinement with logarithmic spacing, discretizing the reservoir to a finer degree region around hydraulic fractures and more coarsely further away from the hydraulic fractures, is coupled with the Forchheimer model to accurately depict the detailed transient fluid flow around the hydraulic fractures [19][20][21]. To obtain the fluid properties, the Peng-Robinson equation of state is employed.…”
Section: Simulation Methodology and Integrated Workflowmentioning
confidence: 99%
“…A literature review on the CO 2 -ESG recovery in shale formation has been conducted . Although data from the literature showed enormous efforts in the understanding of the individual gas (CO 2 and CH 4 ) adsorption in shale, competitive adsorption is not fully understood. More so, shale samples have a stronger affinity to CO 2 compared to CH 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, no study exists on the effect of coupling of competitive adsorption with displacing flow as a key factor in CO 2 -ESGR. Another study 18 showed that the adsorption of CO 2 , CH 4 , and their partitioning is a function of the surface chemistry, pore size, and area of the solid interfaces in the pore system. The authors further demonstrated that preferential adsorption of CO 2 over CH 4 is observed in the cases of silica, Illite, calcite, and kerogen surfaces.…”
Section: ■ Introductionmentioning
confidence: 99%